IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT IN THE BIOMASS VILLAGE MODEL TO IMPROVE PRODUCT QUALITY AND OIL PALM FARMERS’ PERFORMANCE ON RUPAT ISLAND - Eddy Irsan Siregar; Sardiyo; Melly Febriyanti; Dheo Rimbano (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study aims to analyze the implementation of Total Quality Management (TQM) in the Biomass Village model on Rupat Island and its implications for biochar/compost product quality and smallholder oil palm farmer performance. Research Methodology: This study employed a descriptive-applied case study approach conducted in the Biomass Village area on Rupat Island. Data were collected through questionnaires administered to 32 smallholder oil palm farmers, supported by field observations, interviews, and production-process documentation. The study examined the implementation of TQM practices in biochar/compost production and analyzed the relationship between quality management, product quality, and farmer performance using descriptive analysis techniques. Results: The implementation of TQM in the Biomass Village model positively affects the quality of biochar/compost products and improves smallholder oil palm farmer performance through better quality-oriented production management and organizational strengthening. Conclusions: The implementation of TQM in the Biomass Village model positively affects the quality of biochar/compost products and improves smallholder oil palm farmer performance through better quality-oriented production management and organizational strengthening. Limitations: This study is limited to a case study involving 32 farmers within one Biomass Village area on Rupat Island, which may limit the generalization of findings to other agricultural communities or regions. Contributions: This study contributes to the fields of quality management, sustainable agriculture, circular economy, and rural development by demonstrating the practical application of TQM in smallholder farming systems. Pedagogically, the study can also serve as a teaching case for quality management education related to sustainable village development and community-based agricultural innovation.